School Health Unit Implementation - Nami, Rna; Rosmaneli, Rosmaneli; Asmi, Ali (Yayasan Sekora, 2018)
The purpose of this study was to describe the implementation of school health unit (UKS) at SDN 17 Sungai Aur, West Pasaman Regency. The implementation of UKS at SDN 17 Sungai Aur is not going well, this is due to lack of student motivation, lack of support from school principals, lack of school health business development, lack of facilities and infrastructure for fostering school health businesses, lack of role of puskesmas, lack of guidance, lack of cooperation with various related parties, the unhealthy condition of the school environment and the lack of health education and health services.The population of this research was all students in grade V SDN 17 Sungai Aur West Pasaman Regency, amounting to 115 consisting of 58 male students and 57 female students. The sample in this study was taken using purposive sampling technique where the sample in this study was Â± 50% of the population, namely 55 people consisting of 28 male students and 27 female students. The data collection technique used a research instrument questionnaire with a Likert scale, with 4 alternative answers. The results of the data analysis were: (1) The level of success of the implementation of health education at SDN 17 Sungai Aur is in the sufficient classification, namely the level of achievement of the respondents' answers reaching 78.18%. (2) The success rate of the implementation of health services at SDN 17 Sungai Aur is in the adequate classification, namely with an achievement level of 70.18%. (3) The level of the health environment in the implementation of UKS activities at SDN 17 Sungai Aur is in very